A novel triple-mode fluorescent pH probe from monomer emission to aggregation-induced emission1. Issue 12 (11th February 2015) - Wang, Zhenghua; Ye, Jia-Hai; Li, Jing; Bai, Yang; Zhang, Wenchao; He, Weijiang
<x xml:space="preserve">Abstract</x> A tetraphenylenlene (TPE)-based fluorescent probe could selectively monitor pH in THF–H2O media in wide-range pH. From acidic to basic conditions, it displayed monomer emission, ratiometric fluorescence and aggregation-induced emission successively.